Conductance Study of Benzyl Bromide Reaction with Cyclicamines in Aqueous-Ethanol Medium - Radhika, Veerati; ., . (International Journal of Engineering and Technology, 2018)
Nucleophilic substitution reaction of benzyl bromide and cyclicamines in ethanol aqueous intermediate reactivity can suggest that the nucleophile increases through their pKa values. A linear correlation exists between computed values of the dipole moment, rate and electronegativity of the nucelophiles. The two reactants suggest that frontier molecular orbital interactions ion-solvation and correlation of time with the HOMO-LUMO breach of that the reaction.  But it is not orbital controlled as well as forbidden by the electrostatic interactions along with mixed solvent composition between the reactants. The influence on the solvation of ions before reaction has been discuss with facilitate by R-factor. Thermodynamic properties are evaluate and report. The consequences of the learning to be interpreted in terms of ion-solvent exchanges and solvent properties comparing with electrostatic interaction between the reactants.